2014
DOI: 10.3892/mmr.2014.2786
|View full text |Cite
|
Sign up to set email alerts
|

Purification of polysaccharides from Cordyceps militaris and their anti-hypoxic effect

Abstract: Acute mountain sickness, one of the most common altitude diseases, causes lung and brain injury. The present study aimed to investigate the anti‑hypoxic effect of purified polysaccharides extracted from Cordyceps militaris. The aqueous extract of Cordyceps militaris was purified progressively through a DEAE‑52 cellulose anion exchange column and a Sepharose G‑100 column. The fraction CMN1, with a molecular weight of 37842 Da, was the main fraction obtained and its chemical composition and structural characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 28 publications
(28 reference statements)
0
18
0
Order By: Relevance
“…Herbs have become a valuable reservoir for antifatigue agents selection [ 31 ]. In our group, the polysaccharides-enriched Cordyceps militaris extract exhibiting exercise enhancement activity has been successfully demonstrated via modulation AMPK-linked pathway [ 32 ]. The present study aims to investigate the antifatigue effects of Tricholoma matsutake liquid cultured mycelia and fruit body in mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…Herbs have become a valuable reservoir for antifatigue agents selection [ 31 ]. In our group, the polysaccharides-enriched Cordyceps militaris extract exhibiting exercise enhancement activity has been successfully demonstrated via modulation AMPK-linked pathway [ 32 ]. The present study aims to investigate the antifatigue effects of Tricholoma matsutake liquid cultured mycelia and fruit body in mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…Paecilomyces hepiali, purchased from Anhui Agricultural University (Anhui, China; RCEF1429), was cultured in a 100 liter full-automatic fermenter (Biotech-100JS; Baoxing Bioscience Company, Shanghai, China) at 26˚C for 5 days using a defined liquid medium containing 25 g/l sucrose, 10 g/l peptone, 18 g/l yeast extract powder, 3 g/l KH 2 PO 4 , 3 g/l MgSO 4 •7H 2 O, 10 g/l (NH 4 ) 2 SO 4 , 0.01 g/l ZnCl 2 and 0.24 g/l vitamin B 1 (all obtained from Sigma-Aldrich, St. Louis, MO, USA). The mycelia were harvested by centrifugation at 2,667 x g for 10 min at 4˚C, and were lyophilized for further use in a Genesis SQ 25ES lyophilizer (SP Industries, Inc., Warminster, PA, USA) (6). All chemical reagents used in the submerged fermentation were obtained from Sigma-Aldrich.…”
Section: Methodsmentioning
confidence: 99%
“…Polysaccharide-enriched extract, separated from Paecilomyces hepiali (PHC), has been reported as the major active element, which exhibit anti-oxidant activity (3), limit A549 cell proliferation and induce apoptosis (4). In our previous experiments, Cordyceps militaris polysaccharides were confirmed to possess antidiabetic, antinephropathic and antihypoxic activities (5,6). However, the antifatigue and antihypoxic effects of Paecilomyces hepiali mycelium remain to be elucidated.…”
Section: Introductionmentioning
confidence: 96%
“…Our previous study successfully demonstrated that Cordyceps militaris mycelium obtained from submerged fermentation displays excellent antidiabetic and antinephropathic activities [ 16 ]. Purified Cordyceps militaris polysaccharides show the similar antihypoxia effect as rhodiola oral liquid [ 17 ]. However, few studies report the antifatigue effect of Cordyceps militaris .…”
Section: Introductionmentioning
confidence: 99%